FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STATUS GIZI BAYI USIA 0-6 BULAN (STUDI KASUS DI WILAYAH KERJA PUSKESMAS GEBANG, KECAMATAN GEBANG, KABUPATEN PURWOREJO) - Devy Aulia Juniar; Dina Rahayuning Pangestuti; M . Zen Rahfiludin (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Baby’snutritional status is one of public health problems in Indonesia. The result of a preliminary study at the Gebang Community Health Center showed the prevalence of wasting (1.11%), underweight (7,64%) and stunting (2,77%) in 2017. It showed that baby nutrition is a problem in there. The research purpose was to determine the factors related to the nutritional status of babies in the work area of Gebang Health Centre, Purworejo. This research is a quantitative study with a cross sectional design. The population consisted of 75 babies and the sample consisted 46 babies aged 0-6 months taken by simple random sampling technique. The research instrument used baby weight scale, infantometer, KIA book, and questionnaire. Bivariate analysis using Pearson product moment test, rank spearman, and chi square. The result showed that there was a relationship between baby parenting and HAZ (p=0.048), no relationship between baby parenting with WAZ and WHZ(p>0.05), no relationships between Mid-Upper Arm Circumference (MUAC) and Hb levels of pregnant women on their third trimester, exclusive breastfeeding, history of infectious diseases, parenting, clean water sanitation, birth weight, birth height, mothers’ education, and mothers’ occupation with baby nutritional status (p>0.05) and no correlation between pregnant women’s MUAC with baby’s weight and height (p>0.05).There is correlation between Hb levels of pregnant women with baby’s weight(p=0,033).There is no correlation between Hb levels of pregnant women with baby’s height (p>0,05).The mother of baby is expected to pay more attention toparenting and regularly monitor the growth of the baby regularly.